2016
DOI: 10.4103/0972-124x.170815
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal pocket as a potential reservoir of high risk human papilloma virus: A pilot study

Abstract: Aim:Human papilloma viruses (HPVs) are small DNA viruses that have been identified in periodontal pocket as well as gingival sulcus. High risk HPVs are also associated with a subset of head and neck carcinomas. HPV detection in periodontium has previously involved DNA detection. This study attempts to: (a) Detect the presence or absence of high risk HPV in marginal periodontiun by identifying E6/E7 messenger RNA (mRNA) in cells from samples obtained by periodontal pocket scraping. (b) Detect the percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although the US study based on the 2009–2010 and the 2011–2012 NHANES data did not find an association between periodontitis and oral HPV infection (OR = 1.04, 95% CI: 0.63–1.73), periodontitis severity was not assessed in this study [12] . While no HPV-16 was detected in gingival samples from patients with periodontitis in two small studies in India [18] and Brazil [19] , another study in India found HR-HPV in 50% of samples from periodontal pockets [17] . Meanwhile, another study in Finland detected HR-HPV types in 26% of their gingival biopsies suggesting that periodontitis may be a risk factor for oral HPV infection [15] .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although the US study based on the 2009–2010 and the 2011–2012 NHANES data did not find an association between periodontitis and oral HPV infection (OR = 1.04, 95% CI: 0.63–1.73), periodontitis severity was not assessed in this study [12] . While no HPV-16 was detected in gingival samples from patients with periodontitis in two small studies in India [18] and Brazil [19] , another study in India found HR-HPV in 50% of samples from periodontal pockets [17] . Meanwhile, another study in Finland detected HR-HPV types in 26% of their gingival biopsies suggesting that periodontitis may be a risk factor for oral HPV infection [15] .…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it is possible that periodontitis and oral HPV infection are associated through direct effects of the oral microbiota or through the stimulation of chronic inflammation; two mechanisms that could possibly be related [41] . Despite the lack of sufficient scientific evidence in this area, it is important to recognize that the relationship between periodontitis and oral HPV infection may be bidirectional, as recent evidence suggests that viral agents, including HPV, may contribute to periodontitis development [17] , [42] . When HPV infects basal cells, it causes epithelial cell proliferation [43] , disturbance on the odontogenic tissues [44] , and inflammation, which in turn could result in progression to periodontitis [35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingival sulcus has also been implicated as a favored site for the proliferation of pathogenic viruses like Human papillomavirus and Human herpesviruses 6 and 7 [9][10][11][12]. Symbiotic relationship between gingival microbes could be a potential reason for the high viral proliferation in the gingival sulcus.…”
Section: Letter To Editorsmentioning
confidence: 99%
“…The presence of high-risk human papillomaviruses in periodontal pockets patients of diagnosed with chronic periodontitis but not suffering from head and neck squamous cell carcinoma in the present day could link periodontitis to HPV-related squamous cell carcinoma. Prevalence studies detecting the presence of HPV in marginal periodontium as well as prospective studies of HPV-positive periodontitis patients are required to explore this possible link [ 22 ]. The aim of our study was to prove the relationship between periodontitis-causing bacteria and the presence of high-risk HPV genotypes in patients from Bulgaria.…”
Section: Introductionmentioning
confidence: 99%